Preliminary Results of Mapping Capabilities for Agile Software Team Formation - Cunha, Felipe; Santos, Ramon; Perkusich, Mirko; Gorgônio, Kyller; Almeida, Hyggo; Perkusich, Angelo; Albuquerque, Danyllo (Anais do Workshop Brasileiro de Engenharia de Software Inteligente (ISE); 2023: Anais do III Workshop Brasileiro de Engenharia de Software Inteligente, 2023)
Context: Team formation is critical in agile software development, directly affecting project effectiveness and performance. Ensuring teams possess the necessary capabilities is vital for success. However, the specific capabilities used in practice for team composition remain unclear. Aims: Our objective is to understand the evolution, relevance, and practical application of capabilities used in agile team formation and gain real-world insights. Method: We conducted a comparative analysis, contrasting the software engineers’ capabilities identified in a prior review with those used in agile team formation based on recent studies. To gain insights into real-world practices, we interviewed a key practitioner from a software organization through a semi-structured interview. Results: The study highlights the most impactful capabilities for agile team formation, providing valuable guidance for practitioners and researchers to enhance software engineering practices. Conclusions: This research advances the understanding of essential attributes for successful agile team formation and offers valuable implications on underlying aspects and challenges faced in the practical application of these capabilities.